Are Some Mutual Fund Managers Better Than Others? Cross‐sectional Patterns in Behavior and Performance - Chevalier, Judith; Ellison, Glenn (Journal of Finance, 1999)
We examine whether mutual fund performance is related to characteristics of fund managers that may indicate ability, knowledge, or effort. In particular, we study the relationship between performance and the manager's age, the average composite SAT score at the manager's undergraduate institution, and whether the manager has an MBA. Although the raw data suggest striking return differences between managers with different characteristics, most of these can be explained by behavioral differences between managers and by selection biases. After adjusting for these, some performance differences remain. In particular, managers who attended higher‐SAT undergraduate institutions have systematically higher risk‐adjusted excess returns.